Dietary A1 β-casein affects gastrointestinal transit time, dipeptidyl peptidase-4 activity, and inflammatory status relative to A2 β-casein in Wistar rats. (September 2014) - Barnett, Matthew P. G.; McNabb, Warren C.; Roy, Nicole C.; Woodford, Keith B.; Clarke, Andrew J.
Abstract We compared the gastrointestinal effects of milk-based diets in which the β-casein component was either the A1 or A2 type in male Wistar rats fed the experimental diets for 36 or 84 h. Gastrointestinal transit time was significantly greater in the A1 group, as measured by titanium dioxide recovery in the last 24 h of feeding. Co-administration of naloxone decreased gastrointestinal transit time in the A1 diet group but not in the A2 diet group. Colonic myeloperoxidase and jejunal dipeptidyl peptidase (DPP)-4 activities were greater in the A1 group than in the A2 group. Naloxone attenuated the increase in myeloperoxidase activity but not that in DPP-4 activity in the A1 group. Naloxone did not affect myeloperoxidase activity or DPP-4 activity in the A2 group. These results confirm that A1 β-casein consumption has direct effects on gastrointestinal function via opioid-dependent (gastrointestinal transit and myeloperoxidase activity) and opioid-independent (DPP-4 activity) pathways.